Labor Market Concerns and Support for Immigration - Ingar K. Haaland; Christopher Roth (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Do labor market concerns affect support for immigration? Using a large, representative sample of the US population, we first elicit beliefs about the labor market impact of immigration. To generate exogenous variation in beliefs, we then provide respondents in the treatment group with research evidence showing no adverse labor market impacts of immigration. Treated respondents update their beliefs and become more supportive of immigration, as measured by self-reported policy views and petition signatures. Treatment effects also persist in an obfuscated follow-up study. Our results demonstrate that information about the labor market impact of immigration causally affects support for immigration.
Keywords: C91; D83; F22; J15; 330; labor market concerns; support for immigration; political behavior